Management of patients with hypertension and chronic kidney disease referred to Hypertension Excellence Centres among 27 countries. On behalf of the European Society of Hypertension Working Group on Hypertension and the Kidney - Halimi, J.-M.; Nilsson, P.; Vogt, L. (Blood Pressure, 2024)
Objective Real-life management of patients with hypertension and chronic kidney disease (CKD) among European Society of Hypertension Excellence Centres (ESH-ECs) is unclear : we aimed to investigate it. Methods A survey was conducted in 2023. The questionnaire contained 64 questions asking ESH-ECs representatives to estimate how patients with CKD are managed. Results Overall, 88 ESH-ECS representatives from 27 countries participated. According to the responders, renin-angiotensin system (RAS) blockers, calcium-channel blockers and thiazides were often added when these medications were lacking in CKD patients, but physicians were more prone to initiate RAS blockers (90% [interquartile range: 70–95%]) than MRA (20% [10–30%]), SGLT2i (30% [20–50%]) or (GLP1-RA (10% [5–15%]). Despite treatment optimisation, 30% of responders indicated that hypertension remained uncontrolled (30% (15–40%) vs 18% [10%–25%]) in CKD and CKD patients, respectively). Hyperkalemia was the most frequent barrier to initiate RAS blockers, and dosage reduction was considered in 45% of responders when kalaemia was 5.5–5.9 mmol/L. Conclusions RAS blockers are initiated in most ESH-ECS in CKD patients, but MRA and SGLT2i initiations are less frequent. Hyperkalemia was the main barrier for initiation or adequate dosing of RAS blockade, and RAS blockers’ dosage reduction was the usual management. © 2024 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Number of authors = 85 EID = 85197004664 Article no = 2368800 Affiliation = Halimi J.-M., Service de Néphrologie-Hypertension, Dialyses, Transplantation rénale, Hôpital Bretonneau, Tours, France Affiliation = Kreutz R., Institute of Clinical Pharmacology and Toxicology, Charité – Universitätsmedizin Berlin, Corporate Member of Freie Universität Berlin and Humboldt-Universität zu Berlin, Berlin, Germany Affiliation = Vogt L., Department of Internal Medicine, Section of Nephrology, Amsterdam University Medical Center, Amsterdam Cardiovascular Sciences, University of Amsterdam, Amsterdam, Netherlands
Keywords: Chronic kidney disease; guidelines; hyperkalaemia; hypertension; management; mineralocorticoid receptor antagonists; RAS blockers; SGLT2 inhibitors; Angiotensin Receptor Antagonists; Antihypertensive Agents; Calcium Channel Blockers; Europe; Female; Humans; Hypertension; Male; Middle Aged; Renal Insufficiency, Chronic; Societies, Medical; Surveys and Questionnaires; angiotensin receptor antagonist; antihypertensive agent; calcium channel blocking agent; chronic kidney failure; clinical trial; complication; drug therapy; female; human; male; medical society; middle aged; multicenter study; questionnaire